Performance Characterization of Laser Powder Bed Fusion Fabricated Inconel 718 Treated with Experimental Hot Isostatic Processing Cycles - Jaime Varela; Jorge Merino; Christina Pickett; Ahmad Abu-Issa; Edel Arrieta; Lawrence E. Murr; Ryan B. Wicker; Magnus Ahlfors; Donald Godfrey; Francisco Medina (Journal of Manufacturing and Materials Processing, 2020)
Inconel 718 alloy fabricated by selective laser melting (SLM) (or laser powder-bed fusion (LPBF)) has been post-process heat-treated by stress-relief anneal at 1065 °C; stress-relief anneal (1065 °C) + solution treatment (at 720 °C) + aging (at 620 °C); hot isostatic pressing (HIP) (at 1120–1200 °C); stress-relief anneal + HIP; and stress-relief anneal + HIP + solution treatment + aging. Microstructure analysis utilizing optical metallography revealed primarily equiaxed grain structures (having average diameters ranging from ~30 to 49 microns) containing annealing twins, and a high concentration of carbide precipitates in all HIP-related treatments in the grain boundaries and intragrain regions. However, no precipitates nucleated on the {111} coherent annealing twin boundaries because of their very low interfacial free energy in contrast to regular grain boundaries. The mechanical properties for the as-fabricated Inconel 718 exhibited a yield stress of 0.64 GPa, UTS of 0.98 GPa, and elongation of 26%. Following stress-relief anneal at 1065 °C, the yield stress dropped to 0.60 GPa, while the elongation increased to 43%. The associated grain structure was an irregular, somewhat elongated, recrystallized structure. This structure was preserved at a stress anneal at 1065 °C + solution treatment + aging, but grain boundary and intragrain precipitation resulted in a doubling of the yield stress to 1.3 GPa and a reduced elongation of 12.6%. The results of HIP-related post-process heat treatments involving temperatures above 1060 °C demonstrated that the yield stress and elongations could be varied from 1.07 to 1.17 GPa and 11.4% to 19%, respectively. Corresponding Rockwell C-scale hardness values also varied from 33 for the as-fabricated Inconel 718 to 53 for simple post-process HIP treatment at 1163 °C.